The relationship between the expression of lncRNA MALAT1 and clinical features and prognosis in bladder cancer: A meta-analysis: MALAT1 expression and prognosis in bladder cancer - Su, Yi; Chen, Hong; Yao, Lifeng; Dai, Hao; Liu, Houxian (Cellular and Molecular Biology, 2023)
The objective of this meta-analysis is to evaluate the association between LncRNA MALAT1 and the clinicopathological characteristics and prognosis in patients with bladder cancer. Related studies were searched from Pubmed, Embase, Cochrane Library, CNKI and Web of Science up to Sep 1, 2021. Basic characteristic and prognostic data were extracted from the included studies. We synthesized and compared primary outcomes such as overall survival. Based on the cut-off value, sample size, and follow-up time, subgroup analysis was conducted. We calculated the combined hazard ratio (HR), odds ratio (OR), and 95% confidence interval (CI) to assess the relationship between LncRNA MALAT1 and prognosis clinicopathological features of bladder cancer patients. Seven studies with 822 patients were included in this meta-analysis. The results showed that the high lncRNA MALAT1 was significantly related to poor overall survival (HR = 2.34, 95% CI:1.61-3.38; P<0.001) in bladder cancer patients. Furthermore, a high level of LNCRNA MALAT1 is associated with lymph node metastasis (LNM) (OR = 1.82, 95% CI 1.32-2.52, P <0.001) in bladder cancer. The results of sensitivity analysis showed the stabilization and reliability of results in this Meta-analysis. In conclusion, elevated LncRNA MALAT1 is associated with a poor prognosis and a higher risk of LNM in patients with bladder cancer. LncRNA MALAT1 could be identified as a biomarker with a potential prognostic value in bladder cancer.